2020
DOI: 10.1097/md.0000000000020156
|View full text |Cite
|
Sign up to set email alerts
|

Rapid platelet count improvement in chronic hepatitis C patients with thrombocytopenia receiving direct-acting antiviral agents

Abstract: The effect of direct-acting antiviral agents (DAAs) on short-term platelet improvement in chronic hepatitis C (CHC) patients with thrombocytopenia is unclear. From December 2015 to March 2018, a total of 249 CHC patients receiving DAA treatment with baseline thrombocytopenia (platelet count <150 × 103 /μL) at Dalin Tzu Chi Hospital were enrolled in this retrospective study. Blood examinations were conducted at baseline (BL), week 4 (W4) after DAA initiation, end of treatment (EOT), and 12 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 39 publications
0
18
2
1
Order By: Relevance
“…Other BL characteristics were not related to such changes after DAA therapy. This was partly different from our previous study [ 8 ]. Our previous study showed that moderate to severe fatty liver and low BL platelet count could predict significant platelet count improvement.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Other BL characteristics were not related to such changes after DAA therapy. This was partly different from our previous study [ 8 ]. Our previous study showed that moderate to severe fatty liver and low BL platelet count could predict significant platelet count improvement.…”
Section: Discussioncontrasting
confidence: 99%
“…This was thought to be associated with an improved fibrosis stage and portal hypertension [4,5]. Reportedly, thrombocytopenia rapidly improves in CHC patients receiving direct-acting antiviral agents (DAA) [6][7][8][9][10]. However, this improvement, within short-term follow-up, is less likely due to changes in the fibrosis stage [11].…”
Section: Introductionmentioning
confidence: 99%
“…This was partly different from our previous study. 8 Our previous study showed that moderate to severe fatty liver and low BL platelet count could predict signi cant platelet count improvement. The most likely reasons were that some differences existed in the previous study, compared to ndings of the present study, including more case numbers (n = 249), more cancer patients (n = 19 vs. n = 0, P = 0.001), viable HCC patients (n = 14 vs. n = 0, P = 0.013), more advanced hepatic brosis patients (n = 213 vs. n = 72, P = 0.001), and more moderate to severe fatty liver patients (n = 24 vs. n = 5, P = 0.2).…”
Section: Discussionmentioning
confidence: 96%
“…4,5 Reportedly, thrombocytopenia rapidly improves in CHC patients receiving directacting antiviral agents (DAA). [6][7][8][9][10] However, this improvement, within short-term follow-up, is less likely due to changes in the brosis stage. 11 It suggests that factors other than brosis may play important roles, such as hypersplenism, thrombopoietic cytokines, antiplatelet antibody, or direct effect from hepatitis C virus (HCV) via suppressing hematopoiesis.…”
Section: Introductionmentioning
confidence: 99%
“…IFN-free direct-acting antivirals (DAAs) have been the standard treatment for CHC [7][8][9][10]. Platelet count improvement has also been reported, and could be observed within a short-term follow-up period [11][12][13][14][15]. Liver fibrosis status is less likely to improve rapidly and significantly immediately after initiation of DAA therapy [16].…”
Section: Introductionmentioning
confidence: 99%